Dr. Aiman invents laser brazing connection innovation - Safriza, Baharuddin; Nur Hartini, Mohd Hatta (2020)
Pekan, 12 November 2020 - A researcher from the Faculty of Mechanical and Automotive Engineering Technology (FTKMA), Universiti Malaysia Pahang (UMP), Dr. Aiman Mohd Halil, 32 has carried out a research project to improve the quality of brazing joints and reduce the cost of fabrication by implementing material surface texturing technology using laser before the brazing process.